PENGARUH ASIMETRI INFORMASI AKUNTANSI, MANAJEMEN LABA, KUALITAS AUDIT, UKURAN PERUSAHAAN TERHADAP COST OF EQUITY CAPITAL (Studi Empiris Pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia) - B2092171003, Chici Askotamiya (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2019)
ABSTRACT This research aims to analyse the effects of accounting information asymmetry, profit management, audit quality, and company size on cost of equity capital on manufacturing companies registered in Indonesia Stock Exchange from 2013 to 2017. Data analysis techniques consist of descriptive statistics, classical assumption testing, and hypothesis testing with multiple linear regression analysis method. The test results show that information asymmetry has negative effect on the cost of equity capital, profit management and audit quality does not affect the cost of equity capital, and small companies show more significant influence than large companies. The limitation in this study is that the measurement of audit quality variables is only obtained using the standard from public accounting firm, and there are still 89 percent of other factors outside the independent variable which can affect the value of the company’s cost of equity capital. The renewal of this research is to test the data from 2013 until 2017. Keywords: asymmetric, earning management, audit, size, CEC DAFTAR PUSTAKAArens, Alvin. A., Elder, Randal J., Beasley, Mark S., & Amir A. Jusuf. (2009). Auditing and Assurance Services: An Indonesian Adaption. Pearson Prentice Hall.Andriana, D., & Friska, R. (2014). Pengaruh Manajemen Laba, Ukuran Dewan Komisaris, Kepemilikan Institusional, Dan Kualitas Audit Terhadap Biaya Modal Perusahaan. Jurnal Riset Akuntansi dan Keuangan, 2(2), 364-375.Belkoui dan Ahmed Riahi. (2000). Accounting theory, 4th Edition. Thomson Learning.Beneda, N. L. (2003). Estimating cost of capital using bottom-up betas. The CPA Journal, 73(5), 66.Botosan, C. A. (1997). Disclosure level and the cost of equity capital. Accounting review, 323-349.Cornett M. M, J. Marcuss, Saunders dan Tehranian H. (2006). Earnings Management, Corporate Governance, and True Financial Performance. http://papers.ssrn.com/Cuadrado-Ballesteros, B., Garcia-Sanchez, I. M., & Martinez Ferrero, J. (2016). How are corporate disclosures related to the cost of capital? The fundamental role of information asymmetry. Management Decision, 54(7), 1669-1701.Daengs, A., & Sulistyowati, R. (2014). Pengaruh Earnings Management Dan Level of Disclosure Terhadap Cost of Equity Capital Pada Perusahaan Publik Sektor Industri Real Estate Dan Property Di Bursa Efek Indonesia. Bina Ekonomi, 18(1).Dechow, P. M., Sloan, R. G., & Sweeney, A. P. (1995). Detecting earnings management. Accounting review, 193-225.Desiliani, N., & Meiranto, W. (2015). Pengaruh Ukuran Kantor Akuntan Publik, Spesialisasi Industri Auditor Dan Audit Tenure Pada Biaya Modal Ekuitas (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2010–2012) (Doctoral dissertation, Fakultas Ekonomika dan Bisnis).Embong, Z., Mohd-Saleh, N., & Sabri Hassan, M. (2012). Firm size, disclosure and cost of equity capital. Asian Review of Accounting, 20(2), 119-139.Fernando, G. D., Abdel-Meguid, A. M., & Elder, R. J. (2010). Audit quality attributes, client size and cost of equity capital. Review of Accounting and Finance, 9(4), 363-381.Ghozali, Imam. (2009). Analisis Multivariate Lanjutan dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro.Ghozali, Imam. (2011). Aplikasi Analisis Multivariate dengan Program IBM SPSS19 Edisi 5. Semarang: Badan Penerbit Universitas Diponegoro.Hadi, Nor. (2015). Pasar Modal. Yogyakarta: Graha Ilmu.Halim, J., Meiden, C., & Tobing, R. L. (2005). Pengaruh manajemen laba pada tingkat pengungkapan laporan keuangan pada perusahaan manufaktur yang termasuk dalam indeks LQ-45. Simposium Nasional Akuntansi VIII Solo, 117-135.Hartono, Jogiyanto. (2009). Teori Portofolio dan Analisis Investasi, edisi keenam. Yogyakarta: BPFE.He, W. P., Lepone, A., & Leung, H. (2013). Information asymmetry and the cost of equity capital. International Review of Economics & Finance, 27, 611-620.Herusetya, A. (2012). Dapatkah Kualitas Audit Mengurangi Biaya Modal Ekuitas Ex-ante? 1. Jurnal Akuntansi dan Auditing Indonesia, 16(1).Ikatan Akuntan Indonesia. (2002). Standar Akuntansi Keuangan. Jakarta: Salemba Empat.Ifonie, Regina Reizky. (2012). Pengaruh Asimetri Informasi Dan Manajemen Laba Terhadap Cost of Equity Capital Padaperusahaan Real Estate Yang Terdaftar Di Bursa Efek Indonesia. Jurnal Ilmiah Mahasiswa Akuntansi, 1(1), 103-107.Jensen, Michael C. dan W.H. Meckling. (1976). Theory of The Firm: Managerial Behavior, Agency Cost and Ownership Structure. Journal of Financial Economics 3. hal. 305-360.Kieso, D. E., Weygandt, J. J., & Warfield, T. D. (2008). Akuntansi Intermediate Edisi Keduabelas Jilid 1. Jakarta: Penerbit Erlangga.Komalasari, P. T., & Baridwan, Z. (2001). Asimetri Informasi dan Cost of Equity Capital. The Indonesian Journal of Accounting Research, 4(1).Kurnia, L., & Arafat, M. Y. (2015). Pengaruh Manajemen Laba Dan Ukuran Perusahaan Terhadap Biaya Modal Ekuitas Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia. Jurnal Ilmiah Wahana Akuntansi, 10(1), 45-70.Lambert, R. A., Leuz, C., & Verrecchia, R. E. (2011). Information asymmetry, information precision, and the cost of capital. Review of Finance, 16(1), 1-29.Murwaningsari, E. (2012). Faktor-Faktor Yang Mempengaruhi Cost Of Capital. (Pendekatan: Structural Equation Model). Jurnal Ekonomi dan Bisnis Airlangga (JEBA)| Journal of Economics and Business Airlangga, 22(2).Ningsih, R. D., & Ariani, N. E. (2016). Pengaruh Asimetri Informasi, Pengungkapan Modal Intelektual, dan Kualitas Audit terhadap Biaya Modal Ekuitas (Studi pada Perusahaan Lq 45 yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014). Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 1(1), 149-157.Perwira, A. B., & Darsono, D. (2015). Analisa Pengaruh Manajemen Laba Dan Asimetri Informasi Terhadap Cost Of Equity Capital (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2010-2013). Diponegoro Journal of Accounting, 4(4), 31-41.Purwanto, A. (2012). Pengaruh Manajemen Laba, Asymmetry Information, dan Pengungkapan Sukarela Terhadap Biaya Modal. Simposium Nasional Akuntansi XV.R.I., Undang-Undang No. 8 Tahun 1995 tentang Pasar Modal.Samsul, Mohamad. (2006). Pasar Modal & Manajemen Portofolio. Surabaya: Erlangga.Sartono, Agus. (2012). Manajemen Keuangan Teori dan Aplikasi Edisi 4. Yogyakarta: BPFE.Sasongko, N., Admadianto, H. N., & Trisnawati, R. (2016). Effect of Earnings Management, Intellectual Capital Disclosures, Information Asymmetry and Firm Size to Cost of Equity Capital. Proceeding Kuala Lumpur International Business, Economics and Law Conference 11. Bangi, Malaysia.Sawir, A. (2004). Kebijakan Pendanaan dan Restrukturisasi Perusahaan. Jakarta: PT. Gramedia Pustaka Utama.Scott, William R. (2000). Financial Accounting Theory. Second edition. Canada: Prentice Hall.Setiawan, J. A., & Daljono, D. (2014). Pengaruh Kualitas Audit Terhadap Manajemen Laba Dan Biaya Modal Ekuitas. Diponegoro Journal of Accounting, 3(1), 105-113.Sugiono, L. P. (2013). Analisa Faktor yang Mempengaruhi Likuiditas Pada Industri Ritel yang Terdaftar Pada Bursa Efek Indonesia Tahun 2007-2012. Business Accounting Review, 1(2), 298-305.Sugiyono. (2010). Statistika untuk Penelitian. Bandung: Alfabeta.Sujarweni, V. Wiratna. (2014). Metodologi Penelitian Lengkap, Praktis, dan Mudah Dipahami. Yogyakarta: Pustaka Baru Press.Suparno, D. P., & Kiswara, E. (2013). Analisis Hubungan Antara Atribut Kualitas Audit Dengan Biaya Ekuitas Modal (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2011 (Doctoral dissertation, Fakultas Ekonomika dan Bisnis).Suwardjono. (2016). Teori Akuntansi Perekayasaan Pelaporan Keuangan Edisi Ketiga. Yogyakarta: BPFE.Tandelilin, Eduardus. (2001). Analisis Investasi dan Manajemen Portofolio. Yogyakarta: BPFE.Ujiyantho, M. A. (2004). Asimetri informasi dan manajemen laba: Suatu tinjauan dalam hubungan keagenan. Simposium Nasional Akuntansi.Utami, Wiwik. (2005). Pengaruh Manajemen Laba Terhadap Biaya Modal Ekuitas (Studi pada Perusahaan Manufaktur). Makalah dipresentasikan dalam Simposium Nasional Akuntansi VIII. 15 – 16. September: 100 – 116.Vita, E. W. S., Titisari, K. H., & Wijayanti, A. (2018, August). The Effect of Audit Quality Attributes on the Cost of Equity Capital (Empirical Study on Manufacturing Companies Listed In Indonesia Stock Exchange Year 2014-2016). In PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences).Widarjono, Agus. (2015). Analisis Multivariat Terapan: Dengan Program SPSS, AMOS dan SMARTPLS. Yogyakarta: UPP STIM YKPN.Yuvita, S., & Darmawati, D. (2017). Analisis Pengaruh Kualitas Audit Terhadap Manajemen Laba Dan Cost of Equity Capital: Studi Pendekatan Composite Measure. Media Riset Akuntansi, Auditing & Informasi, 13(2), 95-110.